Comparative study of CA19-9 levels as tumor marker in sera and tissues of breast, prostate and thyroid cancer patients - Al-dujaili, A. H.; Al-Taei, W.F.; Turky, K. M.; Al-Ubaidi, G. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Carbohydrate antigen 19-9 (CA 19-9) levels were measured in sera and tissues of 40 patients with breast cancer (01), 8 patients with prostate cancer (G2)and 12 patients with thyroid cancer (G3), by the enzymeÂ linked immunosorbent assay (ELISA) technique.The patients were admitted to Medical City Hospitals (Baghdad Teaching Hospital and Nursing Home Hospital). The sera were taken just before surgery, where the specimens were taken immediately after surgery and kept in saline solution at -20Â°C until the time of homogenizing process.The results of CA 19-9 levels in sera were (16.309Â±7.143; 31.281Â±0.766;11.5Â±0.707 U/ml respectively compared with serum CA 19-9 level of control group G4 which was 7.74:1:4.92 U/ml. The results were found to be significantly higher than control group (p < 0.005).The results of CA 19-9 levels in tissues' homogenate were (30.554 Â± 17.39; 142.375 Â± 8.00; 194.5 Â± 92.4) U/ml. The results revealed significantly higher levels of CA 19-9 in  tissue's homogenate of each patients group compared with the serum levels of the same patients (p < 0.005).